2010
DOI: 10.1007/s12289-010-0922-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the surface quality of the medical implants obtained by single point incremental forming

Abstract: The paper presents a study based on the experimental research on the surface quality of the medical implants used for the partial resurfacing of the femoral condylar surface of the knee obtained by single point incremental forming process. The present paper discusses the measuring of the roughness of parts obtained through the previously mentioned process and highlights the factors that influence it. The initial roughness of the punch, the punch diameter, and the friction coefficient between the punch and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 3 publications
(3 reference statements)
0
19
0
Order By: Relevance
“…In addition, the surface finish decreases with increased tool diameter. Another investigation proved that the equality of formed part (Ti-6Al-4 V sheet) is influenced by the surface roughness of the tool and the friction between the sheet and tool but not by the tool radius [20]. Rough surface of ISF part could be obtained with low feed rate (1200 mm/min) as compared to that obtained with higher feed rate (8400 mm/min) [21].…”
Section: Introductionmentioning
confidence: 92%
“…In addition, the surface finish decreases with increased tool diameter. Another investigation proved that the equality of formed part (Ti-6Al-4 V sheet) is influenced by the surface roughness of the tool and the friction between the sheet and tool but not by the tool radius [20]. Rough surface of ISF part could be obtained with low feed rate (1200 mm/min) as compared to that obtained with higher feed rate (8400 mm/min) [21].…”
Section: Introductionmentioning
confidence: 92%
“…Also, the acetal tool produced a surface that was more cosmetically consistent with unformed sheet metal than the carbide tool. Experimental research was presented by Oleksik et al [85] to study surface quality of the medical implants used for the partial resurfacing of the femoral condylar surface of the knee. The parts made of titanium (Ti-6Al-4V) were manufactured by SPIF.…”
Section: Tool Size and Materialsmentioning
confidence: 99%
“…The tool material and the tool surface quality also influence the final manufactured surface quality. In this way, Oleksik et al [33] reduced the tool roughness in order to improve the part surface finish, and there were obtained a comparable roughness of the final part with the initial roughness of the titanium alloy sheet.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Therefore, springback affects the dimensional accuracy of the finished part. A lot of researchers investigated this topic and they found many solutions to improve the dimensional accuracy of ISF parts: -it is indicated to use a backing plate (Fig.1) to support the sheet flange [4,35]; -using a smaller tool diameter and incremental step depth, the springback can be reduced, as Ambrogio et al [36] and Oleksik et al [33] demonstrated; -Duflou et al [35] concluded that using a multi-pass toolpath strategy leeds to a better accuracy, minimising the sprigback effect. On the other hand Junchao et al [37] find that increasing the number of stages the springback becomes higher using a single stage strategy, because of the springback accumulation during each forming stage;…”
Section: Springback In Isfmentioning
confidence: 99%